2017
DOI: 10.1371/journal.pone.0173605
|View full text |Cite
|
Sign up to set email alerts
|

Maternal vitamin D insufficiency and risk of adverse pregnancy and birth outcomes: A systematic review and meta-analysis of longitudinal studies

Abstract: BackgroundThree previous reviews on the association of vitamin D insufficiency in pregnancy with preterm birth (PTB) and stillbirth were limited in scope and deemed inconclusive. With important new evidence accumulating, there is the need to update the previous estimates and assess evidence on other clinically important outcomes such as spontaneous abortion and Apgar score. We conducted a systematic review and meta-analysis to evaluate the quality and strength of the available evidence on the relations between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
75
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(85 citation statements)
references
References 48 publications
(168 reference statements)
5
75
1
4
Order By: Relevance
“…In pregnant women, levels of 25-OH vitamin D 3 o75 nmol/L (ie, o187 ng/mL [ 748 IU]) are considered a risk factor for certain gestational-associated pathologies. 232 Supplementation in pregnant women with 3800 IU of 25-OH vitamin D 3 ( 1 mg of vitamin) produced encouraging results. 233 All breastfed infants, from mothers successfully supplemented with vitamin D, seem to be warranted for a good health in their lives, although controversial data exist.…”
Section: Pro-survival Features Of Vitamin D: Role In Clinicsmentioning
confidence: 99%
“…In pregnant women, levels of 25-OH vitamin D 3 o75 nmol/L (ie, o187 ng/mL [ 748 IU]) are considered a risk factor for certain gestational-associated pathologies. 232 Supplementation in pregnant women with 3800 IU of 25-OH vitamin D 3 ( 1 mg of vitamin) produced encouraging results. 233 All breastfed infants, from mothers successfully supplemented with vitamin D, seem to be warranted for a good health in their lives, although controversial data exist.…”
Section: Pro-survival Features Of Vitamin D: Role In Clinicsmentioning
confidence: 99%
“…In addition, observational studies with large sample size have shown the association between maternal VDD during pregnancy and increased risk of pregnancy outcomes (Amegah, Klevor, & Wagner, ; Chen et al, ; Wei, Qi, Luo, & Fraser, ), albeit there are still inconsistencies in this regard (Bodnar et al, ; Bomba‐Opon et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The present investigation found that the occurrence of preeclampsia, gestational diabetes, preterm birth, SGA, and caesarean section were not different between groups. The effect of vitamin D supplementation on the pregnancy outcomes including preeclampsia, gestational diabetes, and spontaneous abortion has not been confirmed by several RCTs (Asemi, Karamali, & Esmaillzadeh, 2014b In addition, observational studies with large sample size have shown the association between maternal VDD during pregnancy and increased risk of pregnancy outcomes (Amegah, Klevor, & Wagner, 2017;Chen et al, 2015;Wei, Qi, Luo, & Fraser, 2013), albeit there are still inconsistencies in this regard (Bodnar et al, 2014;Bomba-Opon et al, 2014).…”
Section: Pregnancy Outcomesmentioning
confidence: 99%
“…Recent meta-analyses of observational studies also support that vitamin D insufficiency (<30 ng/dL) is associated with risk of PTB: PTB (<35-37 week, 20-30 ng/dL) RR 1.24 (95% CI 1.04-1.49), PTB (<35-37 week, <20 ng/ dL) RR 1.36 (95% CI 1.04-1.78), PTB (<32-34 week, <30 ng/dL) RR 1.83 (95% CI 1.23-2.74), PTB (<32-34 week, <20 ng/dL) RR 1.86 (95% CI 1.28-2.68) [59]. With regard to spontaneous abortion and stillbirth, the available evidence suggests that there is no association with low vitamin D levels [59].…”
Section: Vitamin D Supplementation During Pregnancy and Preterm Birthmentioning
confidence: 99%
“…With regard to spontaneous abortion and stillbirth, the available evidence suggests that there is no association with low vitamin D levels [59].…”
Section: Vitamin D Supplementation During Pregnancy and Preterm Birthmentioning
confidence: 99%